DESCRIPTION OF SELF-MEDICATION BEHAVIOR IN COMMUNITY OF SUBDISTRICT PURBALINGGA, DISTRICT PURBALINGGA - Ardika Tri Fuaddah (Jurnal Kesehatan Masyarakat (Undip), 2015)
Background : Self-medication is effort to self-medicate using drugs, traditional medicine, or other without advice from health professionals. WHO estimates that more than 50% of drugs prescribed, distributed, or sold inappropriately, and 50% of all patients do not take medication properly and tend to conduct self-medication. Not all prescribed drugs is used accurately and correctly by most people, moreover if the drugs are used to do self-medication . Purpose : The purpose of this study was to describe self-medication behavior on  people in subdistrict Purbalingga, district  Purbalingga. Method : This was a descriptive study  to determine the value of independent variable, either one or more variables (independent) without making comparisons, or proving association between one variable with other variables.  A quantitative study with cross-sectional approach was conducted and used survey as method. Result : Of the total respondents, 56.2% of respondents had bad behavior self-medication, 51.45% of respondents had low knowledge related self-medication and 76.2% have a positive attitude (agree) to self-medication. Respondents chose pharmacy to access medicines (60%). Sources of drug information used to self-medication by respondents came from health care workers (55.7%), personal experience (21.9%), and advertising (21.0%). The average cost incurred respondents to buy drugs used in self-medication was Rp 14264.00 while the distance traveled by the majority of respondents (96.2%) to buy drugs is relatively close (≤2 km). 20.95% received advice from neighbors in doing self-medication and 65.9% do these suggestions. 27.62% of respondents received advice from family in doing self-medication and most (93.1%) do the suggestion.Conclusion : Most respondents still have bad behavior and knowledge about self-medication that needs to be given health education about self-medication.